Pengaruh Brand Awareness, Persepsi Harga, Dan Online Customer Review Terhadap Keputusan Pembelian Produk Pinkflash Kosmetik Di E-Commerce Shopee (Studi Mahasiswi di Kota Malang) - Aishyah, Cholifatul; Basalamah, Muhammad Ridwan; Efendi, Erfan (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to evaluate and explain how brand awareness, price perception, and online customer reviews affect customer decisions to buy pinkflash cosmetic products in shopee e-commerce. The population in this study was female students in Malang city, this study uses a quantitative approach. The sample was determined using the Maholtra formula, resulting in a total of 85 samples. This study uses SPSS 24 for data analysis tools. These include validity, reliability, normality, classical assumptions, hypotheses, multiple linear regressions, and the Adjusted R2 determination coefficient. The results of the study show that brand awareness, price perception, and online customer reviews have a significant simultaneous effect on purchase decisions. However, in non-simultaneous analysis brand awareness does not have a significant effect on purchase decisions, while price perception and online customer reviews play a significant role in purchase decisions. Keywords: Brand Awareness, Price Perceptions, Online Customer Review, Purchase Decision.